EARLY GASTRIC METASTASIS OF BREAST CARCINOMA: REPORT OF A CASE - Emre Ergül; Erdal Gözetlik (European Journal of Breast Health, 2008)

(untitled)
The most common dissemination sites of breast carcinoma are the lungs, bone and liver. Metastatic spread to the stomach may occur many years after the initial treatment for breast cancer. It may prove very diffi cult to distinguish from a primary gastric cancer on clinical, endoscopic, radiological and histopathological features. Here, we present a case of 69 year old woman. Gastric metastasis was detected 6 months after the diagnosis of breast carcinoma. Her resistance to the therapy was costed dear to her.